Motivating Managers to Invest in Accounting Quality: The Role of Conservative Accounting* - Ewert, Ralf; Wagenhofer, Alfred (Contemporary Accounting Research, 2021)
ABSTRACT Although internal control over financial reporting has gained increasing regulatory attention, its enforcement is far from perfect; thus, firm‐specific incentives to management become important to increase the quality of financial reports. We study how owners can motivate managers to invest in accounting quality even though it is costly to the managers. Using an agency model, we establish that a sufficiently conservative accounting system (which understates performance) is necessary to induce a manager to invest in accounting quality, and more conservatism increases this investment. The reason is that higher accounting quality mitigates the expected reduction of the manager's compensation from conservatively measured performance. Higher accounting quality makes the performance measure more precise, and the owner optimally lowers incentives, even though that entails some loss of productivity. In total, more conservatism increases both firm value and accounting quality. Our findings suggest that striving for neutral accounting can counteract incentives to improve accounting quality, and they provide support to using conservatism as a metric of financial reporting quality in empirical studies.